Self-assembled peptide-based supramolecular hydrogel for ophthalmic drug delivery. Issue 80 (11th August 2016) - Liang, Renlong; Luo, Zichao; Pu, Guojuan; Wu, Wei; Shi, Shuai; Yu, Jing; Zhang, Zhaoliang; Chen, Hao; Li, Xingyi
Abstract : Conventional ophthalmic formulations such as eye drops normally suffer from limited therapeutic efficacy with a requirement for frequent instillation. Abstract : Conventional ophthalmic formulations such as eye drops normally suffer from limited therapeutic efficacy with a requirement for frequent instillation. To improve convenience and efficacy, a peptide-based supramolecular hydrogel (Nap-GFFY) was fabricated and tested for ophthalmic drug delivery. Diclofenac sodium (DIC), as a model drug, was encapsulated into the supramolecular hydrogel by simple physical mixing and then thoroughly characterized by transmission electron microscopy (TEM) and rheology. The encapsulated DIC was rapidly released from the supramolecular hydrogel over a period of 24 h study. In vitro cytotoxicity indicated that the developed Nap-GFFY hydrogel was nontoxic against different cell lines (HCEC, HLEC and L929 cells) after incubation for 24 h. Furthermore, an ocular tolerance test suggested that the developed DIC-loaded Nap-GFFY hydrogel gave rise to no eye irritation after a single instillation. More importantly, the drug concentration in the aqueous humor at 1 h after instillation of the DIC/Nap-GFFY hydrogel was significantly higher than that of commercial DIC eye drops (0.1% DIC; w/v), which indicated better corneal penetration and ophthalmic bioavailability. Overall, the developed DIC/Nap-GFFY hydrogel, as a promising ocular formulation, might have potential applications in the treatment of anterior segment disorders.